Electroneutral Polymer Nanodiscs Enable Interference‐Free Probing of Membrane Proteins in a Lipid‐Bilayer Environment. Issue 47 (13th October 2022) - Glueck, David; Grethen, Anne; Das, Manabendra; Mmeka, Ogochukwu Patricia; Patallo, Eugenio Pérez; Meister, Annette; Rajender, Ritu; Kins, Stefan; Räschle, Markus; Victor, Julian; Chu, Ci; Etzkorn, Manuel; et al.
Abstract: Membrane proteins can be examined in near‐native lipid‐bilayer environments with the advent of polymer‐encapsulated nanodiscs. These nanodiscs self‐assemble directly from cellular membranes, allowing in vitro probing of membrane proteins with techniques that have previously been restricted to soluble or detergent‐solubilized proteins. Often, however, the high charge densities of existing polymers obstruct bioanalytical and preparative techniques. Thus, the authors aim to fabricate electroneutral—yet water‐soluble—polymer nanodiscs. By attaching a sulfobetaine group to the commercial polymers DIBMA and SMA(2:1), these polyanionic polymers are converted to the electroneutral maleimide derivatives, Sulfo‐DIBMA and Sulfo‐SMA(2:1). Sulfo‐DIBMA and Sulfo‐SMA(2:1) readily extract proteins and phospholipids from artificial and cellular membranes to form nanodiscs. Crucially, the electroneutral nanodiscs avert unspecific interactions, thereby enabling new insights into protein–lipid interactions through lab‐on‐a‐chip detection and in vitro translation of membrane proteins. Finally, the authors create a library comprising thousands of human membrane proteins and use proteome profiling by mass spectrometry to show that protein complexes are preserved in electroneutral nanodiscs. Abstract : Membrane proteins can be extracted by new electroneutral polymers, along with a disc‐shaped patch of lipid membrane. The resulting electroneutral nanodiscs enable interference‐free probing of protein–lipid interactions with techniques that were previously impossible, such as microfluidic diffusional sizing. The nanodiscs also enable in vitro synthesis of integral membrane proteins as well as the creation of protein libraries from cell membranes.